2016
DOI: 10.1371/journal.pgen.1006277
|View full text |Cite
|
Sign up to set email alerts
|

A Checkpoint-Related Function of the MCM Replicative Helicase Is Required to Avert Accumulation of RNA:DNA Hybrids during S-phase and Ensuing DSBs during G2/M

Abstract: The Mcm2-7 complex is the catalytic core of the eukaryotic replicative helicase. Here, we identify a new role for this complex in maintaining genome integrity. Using both genetic and cytological approaches, we find that a specific mcm allele (mcm2DENQ) causes elevated genome instability that correlates with the appearance of numerous DNA-damage associated foci of γH2AX and Rad52. We further find that the triggering events for this genome instability are elevated levels of RNA:DNA hybrids and an altered DNA top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 87 publications
1
34
0
Order By: Relevance
“…We propose that transcription of the (GAA) 10 repeat generates an R-loop (Fig 7). During replication, the approaching replicative helicase traverses the transcription complex by displacing the RNA polymerase (Pomerantz & O'Donnell, 2010) or by reorganising the helicase itself Vijayraghavan et al, 2016). Biophysical calculations show that DNA:RNA hybrids are sufficiently thermodynamically stable to survive the accumulation of positive supercoiling generated ahead of the replicative helicase (Belotserkovskii et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that transcription of the (GAA) 10 repeat generates an R-loop (Fig 7). During replication, the approaching replicative helicase traverses the transcription complex by displacing the RNA polymerase (Pomerantz & O'Donnell, 2010) or by reorganising the helicase itself Vijayraghavan et al, 2016). Biophysical calculations show that DNA:RNA hybrids are sufficiently thermodynamically stable to survive the accumulation of positive supercoiling generated ahead of the replicative helicase (Belotserkovskii et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…R-loop-accumulating yeast mutants activate the S-phase checkpoint (Gómez-González et al 2009) and head-on T-R conflicts induce ATR checkpoint activation in human cells (Hamperl et al 2017). Furthermore, R-loop-accumulating mutants require a functional S-phase checkpoint to survive (Gómez-González et al 2009), and an MCM-specific mutant impairing its checkpoint activation function was found to lead to R-loop-driven T-R conflicts (Vijayraghavan et al 2016). These results suggest that the replication checkpoint protects against the harmful effect of T-R collisions.…”
Section: Repriming or Arrestmentioning
confidence: 99%
“…DNA–RNA hybrids have been shown to be a replication obstacle (Wellinger et al , ; Gan et al , ; Madireddy et al , ). In the last years, it has been reported that DNA replication‐associated activities, such as those of topoisomerases, MCM2‐7 replicative helicase, and Fanconi anemia proteins, are necessary to prevent transcription–replication conflicts and R‐loop accumulation (Tuduri et al , ; Garcia‐Rubio et al , ; Schwab et al , ; Madireddy et al , ; Vijayraghavan et al , ). Since R‐loops may constitute a major source of replication stress and genome instability (Garcia‐Muse & Aguilera, ), a hallmark of tumor cells (Halazonetis et al , ), deciphering how cells prevent R‐loop accumulation is crucial to understand the origin of genome instability.…”
Section: Introductionmentioning
confidence: 99%